Microbial genome engineering for promoting health and understanding disease - Fehér, Tamás; Györfy, Zsuzsa (Acta Biologica Szegediensis, 2015)
The completion of the first microbial genomes nearly two decades ago opened a completely new chapter in molecular genetics. The availability of precise sequence data permitted the extended use of existing genome engineering methods, and urged the development of a novel set of more rapid and simple techniques for genome editing. The rapidly decreasing price of sequencing and DNA synthesis opened further possibilities of high-throughput genetic analysis and assembly. As a consequence, biomedical knowledge increased at an exponential rate and accelerated the development of numerous connecting fields, including that of medical microbiology. This review presents the reader the toolbox available today to edit and assemble microbial genomes and showcases the key molecular genetic strategies employed to dissect the mechanisms of pathogenesis and construct microbial strains for preventive or therapeutic applications.